액체수소 운송선의 실운항을 위한 규제 분석 및 개정 방향 - 윤동협; 김상현; 박충환; DONGHYUP YOUN; SANGHYUN KIM; CHUNGHWAN PARK (한국수소 및 신에너지학회 논문집, 2025)
Liquid hydrogen offers zero-carbon emissions and high energy density, making it a key fuel for maritime decarbonization. However, its cryogenic properties and flammability pose technical and safety challenges, exposing gaps in current regulations like the High-pressure Gas Safety Control Act and Harbor Act. This study proposes a unified regulatory framework addressing cryogenic storage, boil-off gas handling, and emergency protocols while aligning with international standards such as International Maritime Organization (IMO) and International Organization for Standardization (ISO). These measures aim to ensure safe hydrogen carrier deployment, infrastructure development, and broader hydrogen adoption in the maritime sector.